CusS-CusR Two-Component System Mediates Tigecycline Resistance in Carbapenem-Resistant Klebsiella pneumoniae - Dongjie Chen; Dongjie Chen; Yunan Zhao; Yanqin Qiu; Liying Xiao; Huaqiang He; Dongmei Zheng; Xiaoqin Li; Xiaoli Yu; Nengluan Xu; Xinlan Hu; Falin Chen; et al. (Frontiers in Microbiology, 2020)
BackgroundThe increase in carbapenem-resistant Klebsiella pneumoniae (CRKP), especially the emergence of tigecycline-resistant K. pneumoniae (KP), is a serious public health concern. However, the underlying mechanism of tigecycline resistance is unclear. In this study, we evaluated the role of the CusS-CusR two-component system (TCS), which is associated with copper/silver resistance, in tigecycline resistance in CRKP.MethodsFollowing the in vitro evolution of tigecycline-resistant KP, the minimum inhibitory concentrations of tigecycline were determined using the micro-broth dilution method. RNA sequencing and data analysis were performed to identify differentially expressed genes. Quantitative PCR (qPCR) was performed to verify the genes of interest. Genes associated with tigecycline resistance, such as ramR, tex (T), and tet (A), were detected by PCR, and then mutants were confirmed by sequencing. Additionally, the efflux pump-associated genes soxS, oqxA, oqxB, acrE, and acrF were also analyzed by qPCR. CusR was deleted and complemented by the suicide vector pKO3-Km plasmid and pGEM-T-easy plasmid, respectively.ResultsNine strains of KP were evaluated in our study. Strains A2 and A3 were evolved from A1, B2, and B3 were evolved from B1, and C2 and C3 were evolved from C1. The tigecycline minimum inhibitory concentration for A1, B1, and C1 was 0.5 μg/mL; that for A2, B2, and C3 was 16.0 μg/mL; and that for A3, B3, and C3 was 32.0 μg/mL. RNA-sequencing and qPCR confirmed that the differentially expressed genes cusE, cusS, cusR, cusC, cusF, cusB, and cusA showed higher expression in C2 and C3 than in C1. Genes related to the efflux pump AcrAB-TolC showed higher expression in B2 and B3 than in B1. No mutants of ramR, tex (T), or tet (A) were detected. SoxS, oqxA, oqxB, acrE, and acrF did not show increased expression in any group. After deletion and complementation of cusR among C3, the MIC of tigecycline decreased to 4 μg/mL, and then recovered to 32 μg/mL. The expression of cusFBCA, correspondingly decreased and increased significantly.ConclusionIn addition to its primary function in resistance to copper/silver, the CusS-CusR two-component system is associated with CRKP resistance to tigecycline.